African Biochemists Plan More Collaboration - Peter N. Campbell (The Scientific World Journal)
The Federation of European Biochemical Societies (FEBS) was the first regional organisation of biochemists, holding its first congress in London in 1964. There followed the creation of the Pan American Association of Biochemical Societies (PAABS) and then the Federation of Asian and Oceanian Biochemists (FAOB). An obvious development was the formation of a similar organisation to take care of Africa, but this proved impossible so long as apartheid survived in South Africa. With the removal of the latter, the way was clear for the foundation of the Federation of African Societies of Biochemistry and Molecular Biology (FASBMB). The first congress of the new federation was held in Nairobi in September 1996 under the Presidency of Prof. Dominic Makawiti of Nairobi University. Among the 300 participants were representatives from 19 countries in Africa. The second congress was held at Potchefstroom in South Africa in 1998 and the third was just held in Cairo.